Adventures in reading - Henry (McGraw-Hill, 2002)
Combines adventure-based readings with a picture-dictionary approach to build vocabulary and develop reading and test-taking skills for academic success. This title develops reading comprehension and vocabulary building skills around high-interest reading passages. Read less